PERSPEKTIF FILSAFAT MORAL TERHADAP FAIR PLAY DALAM DUNIA OLAHRAGA MODERN - Hutabarat, Cindy Aulia; Gohae, Gideon; Lumban Gaol, Dita Uli; Halawa, Fiktor Putra Mei Nitema; Hutauruk, Alfrian Sisko; Nurkadri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of modern sports has transformed athletic competition into a global phenomenon that not only emphasizes physical achievement but also highlights the importance of ethical values and moral responsibility. Along with increasing competitiveness, various ethical issues such as doping, match-fixing, unsportsmanlike behavior, and excessive orientation toward victory have become significant challenges in contemporary sports. These conditions indicate the need for a stronger moral foundation to maintain the integrity and educational function of sports. Fair play is one of the fundamental principles that reflects moral values in sports activities and serves as a guide for athletes in conducting themselves ethically during competition. This study aims to examine the concept of fair play from the perspective of moral philosophy and to analyze its relevance within the context of modern sports. The research employs a literature review approach by examining books, scientific journals, and academic publications related to moral philosophy, sports ethics, and fair play. The findings reveal that fair play embodies various moral values, including honesty, responsibility, justice, integrity, respect for others, and self-control. Moral philosophy provides a conceptual framework for understanding fair play not merely as compliance with rules but as a manifestation of ethical awareness and moral commitment. Keywords: Moral Philosophy, Fair Play, Sports Ethics, Modern Sports, Character Education